2003
DOI: 10.1258/026835503321236858
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and histological effects of Dermagraft® in the healing of chronic venous leg ulcers

Abstract: Objective: Pilot study to assess the safety and effectiveness of Dermagraft® when used in conjunction with multi-layer compression bandage therapy (Profore™) compared with multilayer compression only in the treatment of chronic venous leg ulcers. Design: Open-label, prospective, multicentre, randomized, controlled clinical trial. Methods: Patients aged at least 18 years with leg ulceration of venous aetiology were screened for inclusion in the trial. Patients with arterial disease (ankle brachial pressure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Fifty-one articles were retrieved and reviewed in full with 41 rejected on full review. Of the 10 studies that met the inclusion criteria, 5 were used to populate the clinical outcomes of the Markov model [19,20,[33][34][35] and the remaining 5 were used to supply information on health economic, resource utilization, and ulcer recurrence [10,[36][37][38][39]. Where possible, resource utilization data were extracted from the clinical literature.…”
Section: Inclusion Criteriamentioning
confidence: 99%
See 4 more Smart Citations
“…Fifty-one articles were retrieved and reviewed in full with 41 rejected on full review. Of the 10 studies that met the inclusion criteria, 5 were used to populate the clinical outcomes of the Markov model [19,20,[33][34][35] and the remaining 5 were used to supply information on health economic, resource utilization, and ulcer recurrence [10,[36][37][38][39]. Where possible, resource utilization data were extracted from the clinical literature.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Of the four clinical trials [20,[33][34][35], three reported clinical outcomes of ulcer healing at 12 weeks [20,34,35], with one trial having outcomes up to 6 months [33]. The BoxMuller transform method was used to generate random number sampling from the reported means and SDs of the clinical trials [40].…”
Section: Healing Ratesmentioning
confidence: 99%
See 3 more Smart Citations